Growth of Critical Thinking Ability in Middle-School Students: Overview of Discovery Learning Model - Ainiyah, Hidayatul (ETDC: Indonesian Journal of Research and Educational Review, 2024)
This study aims to elucidate the impact of the Discovery Learning model on the critical thinking skills of junior high school students in the eighth grade. This investigation employs a quantitative approach, specifically a quasi-experiment. We conducted this investigation in class 8 of Public Middle School 2 Candi Sidoarjo, utilizing both an experimental and a control group. The results of the data analysis and discussion indicate that teacher activities in social studies learning meet the criteria for both the experimental group and the control class and that student activities in improving students' critical thinking skills in the experimental group are better than the control class. Additionally, at a significance level of 5% (0.05), we observe a significant influence or difference in student responses, with a p-value of 0.000. Therefore, we can conclude that the Discovery Learning learning model significantly influences students' critical thinking skills about the geographical conditions of the ASEAN countries through the atlas, compared to conventional models.